Application of homotopy perturbation method for MHD boundary layer flow of an upper-convected Maxwell fluid in a porous medium - Jhankal, Anuj Kumar (Chemical Engineering Research Bulletin, 2016)
The magneto-hydrodynamics (MHD) boundary layer flow of an electrically conducting upper-convected Maxwell (UCM) fluid in porous medium is studied. The governing similarity equation is solved by Hes Homotopy perturbation method (HPM). The main advantage of HPM is that it does not require the small parameters in the equations and hence the limitations of traditional perturbation can be eliminated. The results reveal that the proposed method is very effective and simple and can be applied to other nonlinear problems. The effects of various physical parameters on the flow presented and discussed through graphs. Chemical Engineering Research Bulletin 18(2015) 12-17